The Elements and Principles of Design: A Baseline Study. (13th June 2013) - Adams, Erin
<x xml:space="preserve">Abstract</x> Critical to the discipline, both professionally and academically, are the fundamentals of interior design. These fundamentals include the elements and principles of interior design: the commonly accepted tools and vocabulary used to create and communicate successful interior environments. Research indicates a lack of consistency in both the identification of what constitutes the elements and principles of design and the specific definitions for each of them. Elements and principles of design vary from textbook to textbook, and this lack of consistency must be addressed when creating a single cohesive interior design vocabulary. This research study sought to gather fundamental information pertaining to the elements and principles of design, such as types of class formats being employed, foundational textbooks utilised, and within each curriculum where the elements and principles were being introduced in CIDA‐accredited interior design programmes. Furthermore, this study assessed the attitudes and perceptions of interior design educators concerning the elements and principles of interior design. The elements and principles of interior design are an integral part of design students' education and will contribute substantially to their skill set in the professional realm. For this reason, it is important that the design elements and principles are taught in a consistent manner, with emphasis placed on their meanings, substance and appropriate applications.